Variability, Heritability, Genetic Gain, Genetic Advance and Correlation in Growth Characteristics of Progenies of Melia azedarach - Thakur, I. K.; Thakur, Shikha (Indian Forester, 2015)
Seeds of Melia azedarach were collected from selected mother trees (ortets) one each at twenty seven locations, and progenies were raised to study the extent and pattern of variation with respect to growth characters. Site S27 (Nauni) exhibited outstanding performance for these traits of progenies followed by S14 (Ropar) and S23 (Subathu), whereas S2(Palu upper) showed the lowest values. High heritability with high genetic gain was observed for collar diameter (0.96 and 64.37 %), root length (0.93 and 57.72 %) and root-shoot length ratio (0.91 and 51.83 %). Highly significant and positive genotypic and phenotypic correlations were observed for majority of the characters. Plant height had significantly positive genotypic and phenotypic correlation with number of branches (0.85 and 0.82) and collar diameter (0.84 and 0.81) whereas collar diameter showed positive and significant genotypic and phenotypic correlation with number of branches (0.83 and 0.74) and number of leaves (0.70 and 0.65).